2019
DOI: 10.1038/s41535-019-0147-2
|View full text |Cite
|
Sign up to set email alerts
|

Fulde–Ferrell–Larkin–Ovchinnikov and vortex phases in a layered organic superconductor

Abstract: Superconductivity is one of the most intriguing topics in solid state physics. Generally, the superconducting Cooper pairs are broken by the Zeeman effect, which gives the so-called Pauli paramagnetic limit H Pauli. However, when the superconductivity is in the clean limit and the orbital effect is strongly quenched, the Cooper pairs can survive even above H Pauli , which is the so-called Fulde and Ferrell, and Larkin and Ovchinnikov (FFLO) phase. Extensive efforts have been devoted to the discovery of the FFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In this intriguing pairing mechanism, the superfluidity "perseveres" in the form of an FFLO state, with a spatial modulation of the phase and amplitude of the order parameter for the FF and LO states, respectively. In the last 55 years many groups have tried to find the FFLO phase experimentally, and some have found only indirect signatures as, for example, in the heavy fermion superconductor CeCoIn 5 , [37][38][39][40][41][42][43][44] organic superconductors, [41,[45][46][47][48][49][50][51][52][53][54][55] as well as iron-based superconductors. [56][57][58] Theoretical studies have found that the FFLO states become unstable in various situations.…”
Section: Introductionmentioning
confidence: 99%
“…In this intriguing pairing mechanism, the superfluidity "perseveres" in the form of an FFLO state, with a spatial modulation of the phase and amplitude of the order parameter for the FF and LO states, respectively. In the last 55 years many groups have tried to find the FFLO phase experimentally, and some have found only indirect signatures as, for example, in the heavy fermion superconductor CeCoIn 5 , [37][38][39][40][41][42][43][44] organic superconductors, [41,[45][46][47][48][49][50][51][52][53][54][55] as well as iron-based superconductors. [56][57][58] Theoretical studies have found that the FFLO states become unstable in various situations.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we clarified the FFLO phase boundary in terms of the magnetocaloric effect, torque [35], and resistance measurements [29]. We also observed the CM effect in fields almost parallel to the a-axis in the FFLO phase, above ∼9 T. The λ FFLO values, ranging from ∼40 nm to ∼210 nm, were obtained under the assumption of a single q vector perpendicular to the field.…”
Section: Introductionmentioning
confidence: 71%
“…The specific-heat measurements show strongly coupled BCS-like behavior with a full gap given by ∆ 0 /k B T = 2.18 [30]. In a magnetic field parallel to the conducting layers, the critical field H c2 significantly exceeded the Pauli limit H Pauli ≈ 10 T, above which the FFLO superconductivity is realized [31][32][33][34][35]. Optical measurements of isostructural β -(BEDT-TTF) 2 SF 5 RSO 3 (R = CH 2 , CHFCF 2 , CH 2 CF 2 , and CHF) compounds revealed that the superconducting phase is adjacent to a chargeordered insulating phase [36].…”
Section: Introductionmentioning
confidence: 95%
“…This finite-momentum of pairs is shared with the concept of superconductivity in a strong uniform magnetic field proposed by Fulde and Farrel [67] and Larkin and Ochinnikov [68]; the difference is the absence of a net magnetic field. (Experimental evidence for a field-induced FFLO state in a layered organic superconductor was reported fairly recently [69,70].) It is also apt to note that there have been other proposals for pairing based on charge-density waves (CDWs) in cuprates.…”
Section: Pdw Ordermentioning
confidence: 96%